Effect of formaldehyde-treated urea on rumen fermentation, ration digestibility and nitrogen utilization - Setälä, Jouko; Syrjälä-Qvist, Liisa (Agricultural and Food Science, 1982)
The study comprises two experiments in which young Finn-sheep were used as test animals. The experimental rations consisted of equal parts of NaOH-treated wheat (Exp. 1) or barley (Exp. 2) straw and a concentrate mixture of barley-molassed beet pulp (Exp. 1) or barley-oats-molassed beet pulp (Exp.2). Feeding was performed twice a day. In addition 20 grams of urea/animal/day was mixed into the concentrates just before feeding. The urea was treated with the following percentages of formaldehyde, on a weight basis: 0 (F0), 1.0 (F1.0), 3.0(F3.0) and 5.0(F5.0) in Exp. 1 and 0, 1.0 and 1.5(F1.5) in Exp. 2. The digestibility of the total ration decreased, when F3.0 and F5.0 urea was used, but the decrease was significant (P< 0.05) only when the apparent digestibility of crude protein was compared between the F0 and F5.0 diets. The amount of rumen bacteria was decreased (P< 0.05) and the amount of protozoa increased (P< 0.01) by formaldehyde treatment levels above F1.0 and F3.0, respectively. The concentration of the total VFA in the rumen tended to decrease with treatment levels higher than F3.0. No significant differences were found in the composition of the VFA. When treated urea was used, the excretion of nitrogen in the faeces increased but its excretion in the urine decreased. The percentage retention of the nitrogen ingested by the animals on diets F0, F1.0, F3.0, and F5.0 in Exp. 1 was 15.0, 10.8, 13.2 and 12.2 and on diets F0, F1.0 and F1.5 in Exp. 2 it was 20.5, 20.2 and 21.2, respectively.